Assessing intercultural communication in oral presentations of students of Architecture in English - Sánchez Carrera, Yanet (Universidad Central "Marta Abreu" de Las Villas, 2013)
In modern society people with different cultural backgrounds are engaged in highly competitive settings and they need to use English language for effective intercultural communication. Students of Architecture at Central University “Marta Abreu” of Las Villas (UCLV) should be able to communicate in English effectively since they are involved in some international collaboration projects with Belgium, Germany and Switzerland where English is used as a lingua franca. They had difficulties in relation to the intercultural awareness necessary to carry out oral presentations about their project designs to succeed in multicultural environments. Since assessment, at a great extent, fosters learning, the overall aim of this research was to provide students of Architecture with the criteria to assess intercultural communication in oral presentations of project designs in English. The proposal included some criteria and rubrics for assessing intercultural communication in oral presentations in this context, a methodology to carry them out and a website that comprised instructional materials for the course English IV.
Keywords: English Language; Effective Intercultural Communication; Architecture Students; English Language; Effective Intercultural Communication; Architecture Students